The effect of cutting and fertilization under controlled conditions on photosynthesis and plant growth of two wet grassland species (Carex canescens and Phalaris arundinacea) representative of the competitive and conservative plant functional types - Angster, Hanna (Jihočeská univerzita, 2023)
Wet grasslands play an important role in the preservation of biodiversity and food production, as they serve as habitat of many birds, insects and other plant species and provide food for farm animals. However, climate change is predicted to affect these wetlands significantly. Therefore, it is important to fully understand the mechanisms of such ecosystems. In this thesis, the effect of fertilization and cutting of the plants on net photosynthesis rate, biomass production and chlorophyll fluorescens of plants of two different plant functional types (PFT) was investigated. The grasses C. canescens, a representative of conservative PFT and P. arundinacea, a competitive species, were used to gain a better understanding on how plants of these PFTs respond to changing environmental conditions and management regimes. We will show that the photosynthesis capacity can differ within the same plant species under different management regimes (water and nutrition level). Additionally, we found that midday depression strongly and significantly influences chlorophyll fluorescens in a way that fertilization treatments can be neglected.
The effect of cutting and fertilization under controlled conditions on photosynthesis and plant growth of two wet grassland species (Carex canescens and Phalaris arundinacea) representative of the competitive and conservative plant functional types
Keywords: C. canescens; P. arundinacea; photosynthesis rate; biomass production; chlorophyll fluorescence; midday depression; C. canescens; P. arundinacea; photosynthesis rate; biomass production; chlorophyll fluorescence; midday depression